2013
DOI: 10.1017/s0007114513001888
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nitric oxide synthase inhibition on glutamine action in a bacterial translocation model

Abstract: Glutamine may be a precursor for NO synthesis, which may play a crucial role in bacterial translocation (BT). The goal of the present study was to investigate the potential effects of glutamine on BT and the immunological response in an experimental model of NO synthase inhibition by NG-nitro-L-arginine methyl ester (l-NAME). Mice were randomly assigned to four groups: sham; intestinal obstruction (IO); IO+500 mg/kg per d glutamine (GLN); IO+GLN plus 10 mg/kg per d l-NAME (GLN/LN). The groups were pretreated f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 52 publications
(62 reference statements)
0
16
0
Order By: Relevance
“…Several studies have shown that β-glucan is very good at improving immunity, and glutamine has an important role in cell-mediated immunity and the integrity of the intestinal mucosa (Sandvik et al 2007, Santos et al 2014, Wang & Ellis 2014, Chaudhry et al 2016, Li et al 2006 . In this report, we demonstrate for the first time the benefits of their association.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several studies have shown that β-glucan is very good at improving immunity, and glutamine has an important role in cell-mediated immunity and the integrity of the intestinal mucosa (Sandvik et al 2007, Santos et al 2014, Wang & Ellis 2014, Chaudhry et al 2016, Li et al 2006 . In this report, we demonstrate for the first time the benefits of their association.…”
Section: Discussionmentioning
confidence: 99%
“…Glutamine is an essential amino acid, it is the most abundant free substance in the plasma and tissue fluids (Bertrand et al 2013, Chaudhry et al 2016. This amino acid is required for specific biochemical processes such as metabolic functions in the immune system and in the intestinal functions (Santos et al, 2014). Glutamine is a precursor to protein synthesis and a preferred energy source for fast proliferation of mucosal cells and cells of the immune system (Bertrand et al 2013).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Notably, plasma D-lactate levels have been found to reflect the permeability and barrier function of intestinal mucosa (24), whereas plasma DAO levels are associated with intestinal mucosal epithelial cell injury and repair (25,26). We observed that Gln supplementation markedly decreased the levels of the aforementioned markers.…”
Section: Discussionmentioning
confidence: 99%